Penentuan Konstanta Laju Pengeringan Coconut Chips - Hary Kurniawan; Sukmawaty Sukmawaty; Ansar Ansar; Kurniawan Yuniarto; Murad Murad; Rahmat Sabani (LPPM Universitas Mataram, 2021)
This study aims to determine the drying rate constant of coconut chips using an oven. Coconut chips drying is carried out at drying temperatures of 50 ° C, 60 ° C and 70 ° C. Drying coconut chips has been conducted at an initial water content of 40-50% wb until it reached ± 10% wb. The change of moisture content was measured every 15 minutes, and the measurement of the water content was determined by the thermogravimetric method. Newton's model was used in determining the observation drying rate constant. Furthermore, the observation drying rate constant was applied to predict the drying rate constant as a function of temperature using the Arrhenius equation. The results showed that the predicted drying rate constants ranged from 0.0090 - 0.0130 minute-1.